Subchronic continuous inhalation exposure to zinc oxide nanoparticles induces pulmonary cell response in mice - Vysloužil, Jan; Kulich, Pavel; Zeman, Tomáš; Vaculovič, Tomáš; Tvrdoňová, Michaela; Mikuška, Pavel; Večeřa, Zbyněk; Stráská, Jana; Moravec, Pavel; Balcar, Vladimir J; Šerý, Omar (Journal of trace elements in medicine and biology, 2020)
OBJECTIVES: We used mice as an animal model to investigate the entry of ZnO nanoparticles from the ambient air into the lungs and other organs, subsequent changes in Zn levels and the impact on the transcription of Zn homeostasis-related genes in the lungs. METHODS: The mice were exposed to two concentrations of ZnO nanoparticles; lower (6.46 × 104 particles/cm3) and higher (1.93 × 106 particles/cm3), allowed to breathe the nanoparticles in the air for 12 weeks and subjected to necropsy. Characterization of the ZnO nanoparticles was done using transmission electron microscopy (TEM). Energy-dispersive X-ray (EDX) spectroscopy was used to quantify ZnO nanoparticles in the lungs, brain, liver and kidney. The total zinc content in the lungs, brain, liver, kidney, red blood cells and plasma was estimated by inductively coupled plasma mass spectroscopy (ICP-MS). Transcription rate of the genes was evaluated by RealTime PCR. RESULTS: The two concentration of ZnO nanoparticles in the ambient air produced two different outcomes. The lower concentration resulted in significant increases in Zn content of the liver while the higher concentration significantly increased Zn in the lungs (p < 0.05). Additionally, at the lower concentration, Zn content was found to be lower in brain tissue (p < 0.05). Using TEM/EDX we detected ZnO nanoparticles inside the cells in the lungs, kidney and liver. Inhaling ZnO NP at the higher concentration increased the levels of mRNA of the following genes in the lungs: Mt2 (2.56 fold), Slc30a1 (1.52 fold) and Slc30a5 (2.34 fold). At the lower ZnO nanoparticle concentration, only Slc30a7 mRNA levels in the lungs were up (1.74 fold). Thus the two air concentrations of ZnO nanoparticles produced distinct effects on the expression of the Zn-homeostasis related genes. CONCLUSION: Until adverse health effects of ZnO nanoparticles deposited in organs such as lungs are further investigated and/or ruled out, the exposure to ZnO nanoparticles in aerosols should be avoided or minimised.
Keywords: zinc; transcription; nanoparticle; inhalation; gene; mouse